Profesjon og ledelse i Den norske kirke Organisering av arbeid i en kirke i endring - Sirris, Stephen (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Ministers, deacons, catechists and cantors are among the church professionals laypeople meet in the context of worship, other church services, and congregational activities. These professionals are upholding a social mission, influencing church practices, setting the tone and developing programs and services within their congregations. What are the hallmarks of the different professions within the church? What insight should church professionals have into each other's identities and areas of expertise to collaborate and participate in interdisciplinary teamwork? And how, in practical terms, should they be lead? Profession and Leadership in the Church of Norway: Organizing Work of a Church in Change provides sociological and administrative insights into general and contextual phenomena in the church professions. Relationships between professions, administration and organization in the Church of Norway are analyzed in light of empirical studies and an institutional theoretical framework. The author discusses how the professions derive appropriate ways of organizing their work. A key finding in the book is that church professions are characterized by calling, autonomy and complexity. These particular features make value-based leadership especially well-suited to the church professions. Part of the work on a new national church law includes addressing central questions about how the Church of Norway, with its extensive range of services and activities, should be led and organized. This book contributes to a broader base of knowledge about administration and the role of the church professions in this complex. Profession and Leadership in the Church of Norway will be of interest to researchers in professional studies and in organization and management, as well as practitioners: employees, church leaders and advisory council members. Thematically, the book is also relevant for students in educational programs that lead to church employment. Stephen Sirris (PhD) is a professor and leader of the Centre for Values-Based Leadership and Innovation at VID Specialized University's Faculty of Theology, Diaconia and Leadership Studies.